Lactobacillus rhamnosus RC007 intended for feed additive: Immune-stimulatory properties and ameliorating effects on TNBS-induced colitis - Dogi, Cecilia Ana (2016)
Lactobacillus rhamnosus RC007 is a potential probiotic bacterium that can exert beneficial effects as supplement for animal feed, by improving the immune status in healthy host, and by providing therapeutic benefits to infected/inflamed animals. The aim of the present work was to evaluate in vivo the beneficial properties of L. rhamnosus RC007, intended for animal feed, when administered to healthy and trinitro-benzene-sulfonic-acid (TNBS) colitis induced BALB/c mice. The administration of L. rhamnosus RC007 to healthy mice during 10 days increased the phagocytic activity of peritoneal macrophages and the number of immunoglobulin A+ cells in the lamina proper of the small intestine. Significant increases of monocyte chemotactic protein 1, interleukin (IL)-10 and tumour necrosis factor alpha (TNF-α) concentrations, and in the ratio between anti- and pro-inflammatory cytokines (IL-10/TNF-α) were observed in intestinal fluids after administration of bacteria. In the inflammation model, less body weight loss, macroscopic and histological damages in the large intestine were accompanied by increased IL-10/TNF-α ratio in the intestinal fluids of mice from the L. rhamnosus-TNBS group when compared to the TNBS group. In a healthy host, the oral administration of L. rhamnosus RC007 kept the gut immune system stimulated allowing a faster response to noxious stimulus. Mice that received L. rhamnosus RC007 also decreased the severity of the intestinal inflammation.